Cholecalciferol effect on oxidative stress and novel predictors of inflammation in hemodialysis patients: a prospective randomized trial - Mona Alshahawey; Lamia Mohamed El Wakeel; Tamer Wahid Elsaid; Nagwa Ali Sabri; Radwa Maher Elborolossy (SpringerOpen, 2024)
Abstract Background Emerging evidence links vitamin D deficiency to oxidative stress (OS) and inflammation, posing ongoing risks to cardiovascular outcomes in hemodialysis (HD) patients. Despite this, current data are lacking regarding the optimal approach or schedule for administering vitamin D in this population. This study investigated the effectiveness of oral weekly versus oral monthly cholecalciferol supplementation on 25-hydroxy vitamin D (25(OH)D) levels, oxidative stress, inflammatory indicators, and secondary hyperparathyroidism in HD population. HD patients (N = 50) were randomly allocated to Group A (oral weekly 50,000 IU cholecalciferol) or Group B (oral monthly 200,000 IU cholecalciferol) for a 3 months duration. Serum levels of 25(OH)D, malondialdehyde (MDA), superoxide dismutase (SOD), high sensitivity C-reactive protein (HsCRP), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and intact parathyroid hormone (iPTH) were assessed at baseline and upon completion of the study. Results A notable increase in serum 25(OH)D levels observed in both groups, with Group A showing a notably greater increase (p = 0.003). Group A demonstrated significant reductions in serum MDA and increases in SOD, along with declines in hsCRP and NLR levels, which were not observed in Group B. Moreover, Group A exhibited a greater drop in iPTH (ΔiPTH = − 30 pg/mL vs. − 3 pg/mL) compared to Group B. Clinicaltrial.gov: NCT05460338, registered 13/07/2022. Conclusions Weekly oral 50,000 IU cholecalciferol supplementation emerges as a tolerable, safe and effective approach for restoring vitamin D levels in HD patients, while concurrently mitigating inflammation, OS, and secondary hyperparathyroidism. This finding suggests that the more frequent the administration of oral cholecalciferol, the higher the efficiency observed.